Investigating the role of emotional intelligence to mitigate the impact of burnout on employees in the Khomas region, Namibia. - Pieters, Wesley; Selma, Ingo; A, Fernandes; E, Ndove (Namibian Journal for Research, Science and Technology, 2022)
The purpose of this study is to investigate whether emotional intelligence has an influence on employee burnout with the employees in the Khomas Region. Employees are faced with constant changes and those with higher emotional intelligence are likely to remain calm and be less affected by these changes. The Emotional Intelligence Questionnaire (EQQ) was used to measure emotional intelligence and the Maslach Burnout Inventory (MBI) was used to measure burnout. Making use of SPSS the data was analysed to assess the relationship. The results showed that a negative correlation exists between emotional intelligence (self-awareness; social skills) and burnout (exhaustion, professional inefficacy, cynicism). This study recommends organisations to host seminars and workshops which can equip their employees with ways on how to cope with stress and challenges, ensuring that the employees’ workload is reasonable and have regular mental health check-ups. Using emotional assessment as part of the recruitment process may ensure that the workforce is able to handle stressful work and be resilient despite experiencing difficult working conditions.